Origin and transformation of light hydrocarbons ascending at an active pockmark on Vestnesa Ridge, Arctic Ocean - Pape, Thomas; Buenz, Stefan; Hong, Wei-Li; Torres, Marta E.; Riedel, Matthias; Panieri, Giuliana; Lepland, Aivo; Hsu, Chieh Wei; Wintersteller, Paul; Wallmann, Klaus; Schmidt, Christopher; Yao, Haoyi; et al. (Journal of Geophysical Research: Solid Earth, 2019)
We report on the geochemistry of hydrocarbons and pore waters down to 62.5 mbsf, collected by drilling with the MARUM‐MeBo70 and by gravity coring at the Lunde pockmark in the Vestnesa Ridge. Our data document the origin and transformations of volatiles feeding gas emissions previously documented in this region. Gas hydrates are present where a fracture network beneath the pockmark focusses migration of thermogenic hydrocarbons characterized by their C 1 /C 2 + and stable isotopic compositions (δ 2 H‐CH 4 , δ 13 C‐CH 4 ). Measured geothermal gradients (~80°C km‐1) and known formation temperatures (>70°C) suggest that those hydrocarbons are formed at depths >800 mbsf. A combined analytical/modeling approach, including concentration and isotopic mass balances, reveals that pockmark sediments experience diffuse migration of thermogenic hydrocarbons. However, at sites without channeled flow this appears to be limited to depths > ~50 mbsf. At all sites we document a contribution of microbial methanogenesis to the overall carbon cycle that includes a component of secondary carbonate reduction (CR) – i.e. reduction of dissolved inorganic carbon (DIC) generated by anaerobic oxidation of methane (AOM) in the uppermost methanogenic zone. AOM and CR rates are spatially variable within the pockmark and are highest at high‐flux sites. These reactions are revealed by 13 C‐DIC depletions at the sulfate‐methane interface at all sites. However, 13 C‐CH 4 depletions are only observed at the low methane flux sites because changes in the isotopic composition of the overall methane pool are masked at high‐flux sites. 13 C‐depletions of TOC suggest that at seeps sites, methane‐derived carbon is incorporated into de novo synthesized biomass.